EVALUASI PROGRAM EKSTRAKURIKULER SENI KEAGAMAAN DI MAN 8 JAKARTA: THE EVALUATION OF RELIGIOUS ART EXTRACURRICULAR PROGRAM AT MAN 8 JAKARTA - Ibnu Salman (Penamas, 2016)
This research aimed to know the context, input, process, and product of religious art extracurricular at the State Islamic Senior High School (MAN) 8 Jakarta. This research used the case study method with the evaluation research model CIPP that it was developed by Stufflebeam and his friends. The CIPP evaluation model included four components, they are context, input, process, and product. The results of this research showed that there was no legal rule of religious art extracurricular activities in context component. In the input component, there were schedule, administration requirements of trainers, academic calendar of religious art extracurricular activities in medium category. In the process component, there were trainers’ smart in learning method on medium level, but there was no indicator on medium category in the product component. By the other words, there was only high category in product component. Keywords: Extracurricular education, religious art education, CIPP, MAN 8 Jakarta Penelitian ini bertujuan untuk mengetahui konteks, input, proses, dan produk ekstrakurikuler seni keagamaan yang ada di Madrasah Aliyah Negeri 8 Jakarta (MAN 8 Jakarta). Metode penelitian yang digunakan adalah studi kasus (case studies), dengan model riset evaluasi CIPP yang dikembangkan Stufflebeam dan kawan-kawan. Evaluasi model CIPP terdiri dari empat komponen, yaitu: context, input, process, dan product. Hasil penelitian mengungkapkan, bahwa pada komponen konteks terdapat landasan hukum kegiatan ekstrakurikuler seni keagamaan yang belum ada, pada komponen input terdapat perencanaan atau penjadwalan, persyaratan administrasi pelatih, dan kalender akademik kegiatan ekstrakurikuler seni keagamaan berada pada katagori sedang. Pada komponen proses, terdapat penguasaan metode pembelajaran oleh pelatih berada pada katagori sedang, dan pada komponen produk tidak terdapat indikator yang sedang, atau dengan kata lain pada komponen produk, penilaian yang didapat, yaitu pada katagori tinggi. Kata Kunci: Pendidikan ekstrakurikuler, pendidikan seni keagamaan, CIPP, MAN 8 Jakarta